(untitled) (Herald of the National Children’s Medical Center, 2025)
With congenital heart defects (CHD) with pronounced shunts from left to right, heart failure is often observed from the first days of a child’s life, leading to the development of severe pulmonary hypertension (PH). In most of these patients, the pressure level in the pulmonary artery (PA) reaches 91-100% of the pressure in the aorta. These patients need urgent surgical correction. Despite significant progress in cardiac surgery, no universal algorithms have been developed for the management of such patients. Of particular importance is the method of direct measurement of pressure in the LA with an assessment of the response to vasodilators.